2014
DOI: 10.1128/mbio.01019-13
|View full text |Cite
|
Sign up to set email alerts
|

Laser Optical Sensor, a Label-Free On-Plate Salmonella enterica Colony Detection Tool

Abstract: We investigated the application capabilities of a laser optical sensor, BARDOT (bacterial rapid detection using optical scatter technology) to generate differentiating scatter patterns for the 20 most frequently reported serovars of Salmonella enterica. Initially, the study tested the classification ability of BARDOT by using six Salmonella serovars grown on brain heart infusion, brilliant green, xylose lysine deoxycholate, and xylose lysine tergitol 4 (XLT4) agar plates. Highly accurate discrimination (95.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 47 publications
(76 reference statements)
2
65
0
Order By: Relevance
“…We observed that the scatter patterns of the WT and mutant strains were different on BHIA and LBA but were similar on different brands of BHIA. It has been reported in our previous studies that bacterial colony scatter patterns vary with the growth medium used (5,7,9,11). Thus, we expect that any mutation in the genes involved in the biochemical pathways for substrate utilization will also result in differential scatter patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the scatter patterns of the WT and mutant strains were different on BHIA and LBA but were similar on different brands of BHIA. It has been reported in our previous studies that bacterial colony scatter patterns vary with the growth medium used (5,7,9,11). Thus, we expect that any mutation in the genes involved in the biochemical pathways for substrate utilization will also result in differential scatter patterns.…”
Section: Discussionmentioning
confidence: 99%
“…BARDOT proved to be useful for studying the streptomycin-induced stress response in Salmonella enterica serovar Typhimurium (12) and as a bioanalytical detection tool to validate the performance of a sample processing and enrichment device, i.e., PED (pathogen enrichment device) (13). BARDOT-generated colony scatter phenograms exhibited strong relationships with the genotypes of bacteria (5), suggesting that BARDOT can be used to screen mutant strains that are deficient in specific virulence genes. In the present study, we used Listeria monocytogenes as a model pathogen and used BARDOT to screen mutant strains that are deficient in specific virulence genes.…”
mentioning
confidence: 99%
“…Over the last several decades, there have been significant developments in rapid Salmonella detection methods using multiple novel approaches reducing preenrichment or detection time (e.g., In-situ immuno-gold nanoparticle network ELISA biosensors, immunomagnetic separation, automated microfiltration system, pathogen enrichment device, laser optical sensor, modified media, isothermal amplication) [79][80][81][82][83][84][85][86][87][88][89]. (Figure 2).…”
Section: Salmonella Detectionmentioning
confidence: 99%
“…One major recent development has been the reports of the use of an enzyme based approach coupled to a short enrichment and microfiltration steps for reducing time for sample preparation. This allowed Salmonella to be detected at very low levels (≤ 1 CFU/g) in different contaminated foods in 8 hours or less than one work shift [82][83][84]. The major concept is shown in Figure 3.…”
Section: Salmonella Detectionmentioning
confidence: 99%
“…Our technique uses back scatter spectra from a tissue surface, unlike Mie scatter imaging which uses forward scatter images through colonies to identify patterns 21 . Mie scatter imaging systems, often referred to as BARDOT systems, require bacteria to be cultured on before identification of bacterial species, as BARDOT systems are used to identify fully developed cultures on an optically transparent substrate 22,23,24 . The system designed here does not require the additional steps of culturing a wound sample to determine the presence or cause of bacterial infection.…”
Section: Introductionmentioning
confidence: 99%